Langkah Pemerintah Menangkal Diseminasi Berita Palsu - Prayitno, Budi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2017)
The spread of hoaxes in social media has raised some concerns. Various efforts have been made by the government to minimize its distribution. However, a number of cases related to hoaxes that contain slander and hatred of the Ethnic, Religion, and Race increase over the past three years. This research seeks to find out what strategic and policy steps have been taken by the government. The results show that the government attempted to minimize the distribution of hoax by issuing a number of regulations and supporting infrastructure. That regulation is not optimal because there are some weaknesses contained in the regulation. The existing regulations only address a number of anticipatory steps that must be taken and do not address the root causes of the spread of hoax. On the other hand, the government is also not optimal in coordinating across agencies. And, the government is not optimal to provide media literacy to the community of social media users. Media Literacy is important to make media users have the ethic when interacting in cyberspace